Profile of Dermatologic Side Effects of Tyrosine Kinase Inhibitor (EGFR-TKIs) in Lung Cancer Patients - Napitupulu, Elfrida; Nurrochmad, Arief; Hanafi, Arif Riswahyudi; Wahyudi, Danang Tri (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor (EGFR-TKIs) drugs are commonly used target therapies in patients with advanced-stage non-small cell carcinoma lung cancer (NSCLC).Objectives: This study aims to provide an overview of dermatologic side effects and quality of life index of NSCLC patients who received EGFR-TKIs targeted therapy at Dharmais Cancer Hospital.Methods: This study used a cross-sectional design. Inclusion criteria were patients who received EGFR-TKIs targeted therapy, namely gefitinib, erlotinib, and afatinib, in September - October 2023, who were willing to be research subjects, and patients who were not in a medical emergency. In total, 52 patients filled out the dermatology life quality index (DLQI) questionnaire through interviews and medical records. Data evaluation was performed descriptively in the form of percentages.Results: The most common occurrence of dermatologic side effects was skin hypersensitivity reactions with mild severity (grade 1) by 59.6%, moderate severity (grade 2) by 19.2%, and severe severity (grade 3) by 1.9%, and no drug dermatologic side effects by 19.2%. In comparison, the most DLQI was in the category of not affecting patient life. In general, side effects with moderate (grade 2) and severe (grade 3). The severity will decrease to mild severity (grade 1) when already getting topical corticosteroid drugs or combinations with oral antibiotics and antihistamine drugs.Conclusion: The most severe side effect was grade 1, which slightly affected the patient's quality of life. Education and monitoring of side effects and management of symptoms are necessary to reduce the severity and improve patients' quality of life.